Mempertahankan Budaya Leluhur Melalui Sosialisasi Perahu Beganduang : Upaya Pelestarian Kearifan Lokal di SDN 42 Pekanbaru - Indah Putri Alwiyah S; Ilham Hudi; Resty Amanda Zainal; Hafidatul Husna; Rifna Angraini (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This community service program aims to introduce and preserve local culture by educating elementary school students at SD Negeri 42 Pekanbaru about the Beganduang boat. The Beganduang boat is a unique cultural heritage from Lubuk Jambi, Kuantan Singingi Regency (Kuansing), which holds significant historical and philosophical value in the local community's life, particularly in river transportation and traditional ceremonies. The awareness-raising activity was attended by 40 students, accompanied by 4 teachers, including the principal of SD Negeri 42 Pekanbaru. The materials presented included the history, cultural significance, and the process of making and using the Beganduang boat in the daily life of the Lubuk Jambi community. The methods used included interactive lectures, discussions, and the screening of visual media such as images and documentary videos of the Beganduang boat. The results of the activity showed that the students were enthusiastic about participating in the socialization, as evidenced by their high level of active participation in the question-and-answer session and their ability to recall the distinctive features and cultural values of the Beganduang boat. This activity is hoped to foster awareness among the younger generation to love, preserve, and protect the local wisdom of their region as part of the nation's cultural identity.